Hubungan Antara Kecemasan Dengan Kejadian Hipertensi Pada Lansia Di Panti Sosial Tresna Werdha Puspakarma Mataram - Uswandari, Baiq Dian; , Setia Asyanti, S.Psi M.Si (2017)
ABSTRACT This study aims to determine the relationship between anxiety with hypertension in the elderly in Social Institutions Tresna Werdha Puspakarma Mataram. The hypothesis of this study is that there is a positive relationship between anxiety with hypertension in the elderly. Subjects in this study amounted to 76 elderly. Data collected by the anxiety scale Hars and tension. Data analysis technique used is the correlation of Pearson Product Moment. Based on the results obtained there is a significant positive relationship between anxiety with hypertension in the elderly, and the effective contribution of anxiety to hypertension of 7.07%. Researchers give suggestions for subjects to be able to control his anxiety, which can make blood pressure became normal. Keywords: Anxiety, Hypertension, Elderly